Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

evaluate the expression when f=6 12f+3

Sagot :

Answer:

75

Step-by-step explanation:

Substitute 6 for f

12f+3=

12*6+3=

72 + 3 = 75

Answer:

12f+3 = 75 when f = 6

Step-by-step explanation:

12f+3

Let f = 6

12*6+3

Multiply

72 +3

Add

75